Kajian Etnobotani Pengetahuan dan Pemanfaatan Sumber Daya Tumbuhan Masyarakat Dayak Taboyan, Kecamatan Gunung Purei, Kabupaten Barito Utara, Kalimantan Tengah - Wardah; Marwan Setiawan (Journal of Tropical Ethnobiology, 2021)
This study aims to reveal the use of plants and the knowledge of the Taboyan Dayak community in Gunung Purei District, North Barito Regency on their environment. The methodology used is ethnoscience, meaning that the implementation of this method includes two aspects: 1. Inventory of all types of plants used, including local names, identification of scientific names and their uses; 2. Studying the interactions between people and the environment in which they live, meaning that we study the biological and social aspects. Data collection was conducted by interviewing selected resource persons with the Head of Customary Affairs, Customary Heads, community leaders, District Offices, and people who understand about nature and the environment. The results show that the Taboyan Dayak community has a very close relationship with nature and the environment, which is reflected in various knowledge about the use of plant resources in daily life. There were 79 types of plants used by the community, the uses were categorized as vegetables (25 species), fruits (22 species), food ingredients (14 species), ritual materials (12 species, and medicinal ingredients (9 species). The natural environment is reflected in the protected forest area of Mount Lumut which is sacred because it is the place where the spirits of the Hindu Kaharingan religion who have died stop before going to heaven or meeting Ranying Hattalata.